2009
DOI: 10.1037/a0016165
|View full text |Cite
|
Sign up to set email alerts
|

Anxious solitude and peer exclusion predict social helplessness, upset affect, and vagal regulation in response to behavioral rejection by a friend.

Abstract: Abstract:Competent social interaction requires adaptive responding to occasional social challenges-for instance, having a social invitation declined by a social partner. This investigation examined the propensity for anxious solitary children to respond adaptively or helplessly to an instance of perceived behavioral rejection by a friend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
122
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 66 publications
16
122
3
4
Order By: Relevance
“…However, those who manage to achieve a dominant position show lower heart rates. In humans, it was observed that anxious solitary children that were often excluded had more sustained acceleration in heart rate during a rejection experiment compared with anxious solitary children not often excluded (Gazelle and Druhen 2009). These findings are consistent with others showing that subordinate status is associated with increased heart rate and readiness to meet threats.…”
Section: Discussionsupporting
confidence: 81%
“…However, those who manage to achieve a dominant position show lower heart rates. In humans, it was observed that anxious solitary children that were often excluded had more sustained acceleration in heart rate during a rejection experiment compared with anxious solitary children not often excluded (Gazelle and Druhen 2009). These findings are consistent with others showing that subordinate status is associated with increased heart rate and readiness to meet threats.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, lower RSA has been linked with anxiety in adolescents (GreavesLord et al 2007). Third-graders nominated by peers as anxious-solitary and excluded exhibited lower RSA during a friend-rejection protocol, compared to anxious-solitary (but not excluded) children (Gazelle and Druhen 2009). Although reduction in RSA (vagal withdrawal) in response to peer provocation and cognitive challenges has been linked with emotion regulation (Hessler and Katz 2007) and social skills in children (Graziano et al 2007), lower RSA during social interaction may reflect emotional arousal that is less compatible with positive social engagement and more compatible with social disengagement or defensiveness (Hastings et al 2008).…”
Section: Physiological Arousal and Regulationmentioning
confidence: 91%
“…As such, HR is a less precise measure of underlying physiological processes, but may be experienced more subjectively (i.e., felt) than other ANS indices. Gazelle and Druhen (2009) reported that anxious-solitaryexcluded children exhibited lower heart period (higher HR) before and during a friend-rejection protocol, compared to children who were either anxious-solitary or excluded. Other research has documented relations between internalizing and HR accelerations during social or emotional challenges (Hastings et al 2007;Weems et al 2005).…”
Section: Physiological Arousal and Regulationmentioning
confidence: 97%
See 1 more Smart Citation
“…As an illustration, most individuals would agree that, from a moral viewpoint, one should not cooperate with others to commit acts of terror, to deny necessary resources to those in need, or to intentionally commit unprovoked aggression. Malevolent forms of cooperative activities are not the sole province of adulthood; children also cooperate with others to ostracize or exclude peers from group activities [Gazelle & Druhen, 2009;Killen & Rutland, 2011;Salmivalli, Voeten, & Poskiparta, 2011].…”
Section: Morally Repugnant Forms Of Cooperationmentioning
confidence: 99%